Reformulasi Politik Hukum Agraria - Margarito Kamis (Jurnal Hukum IUS QUIA IUSTUM, 2000)
It is thought that the reformulation of the political agrarian is urgently, seriously and effectively managed. This reformulation is required firstly because the political changes, during the New Order regime with its 'developmental ideologi, have ever destroyed the regulations of legal agrarian. Secondly, it is intended to enable the social welfare and human values to be appropriately constructed. The fundamental weaknesses of the Basic Principle of Agrarian Law and the changing bases of the facets of material, social, economy, political and legal customs are also regarded as apart of the opinion of why the political reformulation of the legal agrarian must be enforced immediately. The main point of the reformulation is also concerned with the position of Legal societies and nations, and is should be framed on the equaiity paradigm in law. Another point is that reconstruction of the regulations of authority and land ownership.